ChemInform Abstract: Photo‐Induced Metal‐Catalyst‐Free Aromatic Finkelstein Reaction. Issue 50 (December 2015) - Li, Lu; Liu, Wenbo; Zeng, Huiying; Mu, Xiaoyue; Cosa, Gonzalo; Mi, Zetian; Li, Chao‐Jun
Abstract: A photo‐induced halogen exchange in aryl or vinyl halides affording aryl or vinyl iodides under mild reaction conditions is presented.